2013
DOI: 10.22278/2318-2660.2012.v36.n3.a561
|View full text |Cite
|
Sign up to set email alerts
|

Internato De Medicina Social Em Uma Unidade De Saúde Da Família

Abstract: O internato médico é o período do curso de medicina em que o estudante vivencia prática médica diária, inserido nas  instituições de saúde, como componente curricular obrigatório na sua formação. O objetivo deste trabalho foi relatar a experiência de dois estudantes do 5º ano do curso médico da Faculdade de Medicina da Bahia, da Universidade Federal da Bahia (UFBA), no Internato em Medicina Social em uma Unidade de Saúde da Família. Foram realizadas atividades em uma Unidade de Saúde da Família, centradas nos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…31 Furthermore, HBOT increases the partial pressure of oxygen in the tissues, promoting a high availability of oxygen and subsequent stimulation of fibroblast proliferation and collagen synthesis, osteoblastic activity in irradiated areas, angiogenesis and reepithelialisation, and the bactericidal/bacteriostatic effect, as well as synergism with some antibiotics in the treatment of local infections of the oral cavity. 1,32,33 In 1976, Hart and Mainous 34 suggested that the beneficial action of HBOT was due to the angiogenic and cell proliferation effects. Marx et al 35 published experimental work on an animal model (rabbit) in which, after 20 sessions of HBOT (2.4 ATA, 90 minutes daily), was observed increase of 8 to 9 times more in vascular density compared to controls under normobaric oxygen or air-breathing (p-value= 0.001).…”
Section: Hyperbaric Oxygen Therapymentioning
confidence: 99%
“…31 Furthermore, HBOT increases the partial pressure of oxygen in the tissues, promoting a high availability of oxygen and subsequent stimulation of fibroblast proliferation and collagen synthesis, osteoblastic activity in irradiated areas, angiogenesis and reepithelialisation, and the bactericidal/bacteriostatic effect, as well as synergism with some antibiotics in the treatment of local infections of the oral cavity. 1,32,33 In 1976, Hart and Mainous 34 suggested that the beneficial action of HBOT was due to the angiogenic and cell proliferation effects. Marx et al 35 published experimental work on an animal model (rabbit) in which, after 20 sessions of HBOT (2.4 ATA, 90 minutes daily), was observed increase of 8 to 9 times more in vascular density compared to controls under normobaric oxygen or air-breathing (p-value= 0.001).…”
Section: Hyperbaric Oxygen Therapymentioning
confidence: 99%